1992
DOI: 10.1038/sc.1992.102
|View full text |Cite
|
Sign up to set email alerts
|

Breathing pattern adjustments during the first year following cervical spinal cord injury

Abstract: The alterations in lung function and breathing pattern were examined in 6 quadriplegics at 3, 6 and greater than 12 months post injury, and were compared to 6 able bodied controls. Subjects were studied in both the seated and supine positions. Functional residual capacity (FRC), forced vital capacity (FVC), inspiratory capacity (IC), and maximum mouth pressure (Pimax) at FRC were measured. Total lung capacity (TLC) and residual volume (RV) were calculated. Resting breathing pattern was assessed for 20 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…22,23 Our findings are in accordance with experimental data previously reported in unilateral C5 contusion 8 and bilateral cervical contusion 9,10 paradigms. Most of these studies demonstrated transient changes in respiratory rate and tidal volume under normoxic conditions, but no effects on global minute ventilation.…”
Section: Discussionsupporting
confidence: 83%
“…22,23 Our findings are in accordance with experimental data previously reported in unilateral C5 contusion 8 and bilateral cervical contusion 9,10 paradigms. Most of these studies demonstrated transient changes in respiratory rate and tidal volume under normoxic conditions, but no effects on global minute ventilation.…”
Section: Discussionsupporting
confidence: 83%
“…This improvement can be due to an increased elastic recoil of the lungs, resulting from a high FVC. The increase in MEP observed by other authors is related to specific expiratory muscle intervention, (4,9,29) which did not occur in our study, because the protocol was applied to the inspiratory muscles only.…”
Section: Resultsmentioning
confidence: 49%
“…According to one group of authors, (4) the tonus of the abdominal muscles increases by approximately 3 months after the lesion, and that, at one year after the injury, pulmonary function can improve in relation to the initial phase and tends to become stable. (3,28) In our study, none of the patients was in the acute phase, since the duration of the lesion ranged from 35 to 318 months, and, although there was no control group, spontaneous improvement is not probable in this phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncommon to find P Emax inferior to P Imax even if in some neurological diseases, such as cervical spinal cord injury, 59 P Emax is typically more reduced than P Imax . Different studies reported varying normal values for P Imax and P Emax that are lower in females and fall with advancing age with large SD values of the data, which mean that lower limits of normality are approximately 50% of predicted normal values.…”
Section: Airway Pressure and Flowmentioning
confidence: 99%